Ideowe i edukacyjne aspekty budowania ukraińskiej niepodległości w XIX wieku - Kowacki, Karol (Chowanna, 2022)
. The article focuses on the ideological and educational aspects of selected Ukrainian-centric thinkers and activists. Without the ideological and educational activities of this small group of the emerging Ukrainian intelligentsia, the million ethnic Ukrainian masses would have been absorbed into the Polish or Russian nationality project. The text presents the basic ideological principles that are the basis for shaping national consciousness and describes adverse historical conditions causing difficulties in shaping the Ukrainian idea of independence. The implementation of Ukrainian-centric ideas is shown on the example of selected organizations and representatives of Ukrainian culture, such as The Brotherhood of Saints Cyril and Methodius, Hromada, Stara Hromada, Panteleimon Kulish, Mykola Kostomarov, Volodymyr Antonovych, Mykhailo Drahomanov. The aim of the article is to present the importance of education in the process of formation of national consciousness.